Local Memory and Urban Space - Łupienko, Aleksander (Acta Poloniae Historica, 2023)
The paper ponders over the issue of memory and urban space. It shows how these categories have been discussed in the literature and how they are connected to the problem of place identity. The paper also highlights the need to appreciate and assess the physical aspect of objects, which act as memory markers in the urban space. The author argues that what is being memorialised and conveyed as meaning is the past lived experience. As a case in point, two memory acts are analysed in the paper, clearly showing the interdependence of various temporalities in the anniversary celebrations. In the festivities celebrating the 100th (in 1881) and 150th (in 1931/2) anniversaries of the consecration of the Lutheran church in Warsaw, the capital of the Kingdom of Poland in the Russian partition and later the capital of a resurrected independent Polish state after 1918, the different present-oriented needs were mirrored in the narratives and commemorations of the past. Idiosyncratic visions of the past help make the small and vulnerable community of Lutherans in an otherwise primarily Roman Catholic environment more coherent, as its members may lay claim to history and construct and stabilise their identification process as descendants of past generations. Moreover, the material fabric of the church seems to be an indispensable factor. The parishioners’ lived experience appears to be a crucial component of commemorations in the late nineteenth and early twentieth centuries.